Selective electrocatalytic nitrate reduction to dinitrogen: Mechanisms, catalysts, and challenges - Jiayu Chen; Anni Wu; Yongfeng Xie; Yumin Zhang; Hu Zheng; Wei Teng (Electrochemistry Communications, 2025)
Electrocatalytic reduction of nitrate to dinitrogen (N2) offers a sustainable, carbon-neutral approach to mitigate nitrate pollution by transforming nitrate into an environmentally benign end-product. While extensive research has focused on ammonia production, selective N2 production remains challenging due to complex pathways, limitations in detection, and the difficulty of controlling reaction on the electrocatalysts. This review provides an overview of current progress in this field, focusing on mechanistic insights, N2 detection methods, and advances in catalyst design. Various classes of electrocatalysts, including monometallic, bimetallic, and single-atom systems, oxide-based and carbon-based materials, examining how their structures regulate key intermediates and NN coupling. The influence of operational parameters such as applied potential, electrolyte, pH, and reactor design is also reviewed. Despite significant advances, challenges remain in understanding interfacial mechanisms and achieving high N2 selectivity under realistic conditions. This review aims to offer timely insights and guidance for the future development of efficient electrocatalytic systems toward selective nitrate-to-N2 conversion, advancing environmental remediation and sustainable nitrogen management.